PROBLEMATIKA PENDIDIKAN DASAR ISLAM ABAD 21 DI SD NEGERI KENTUNGAN YOGYAKARTA - Dewi Sutilah (LPPM Institut Pendidikan Nusantara Global, 2021)
This study aims to analyze the problems of 21 st Islamic basic education problems in Kentungan State Elementary School and how the principal’s contribution in dealing with these problems in order to achieve effective and efficient learning goals and realize the goals of Indonesia’s national education. The research method used is descriptive qualitative. The results showed that there were several problems as follows: (1) lack of character education (2) lack of supporting facilities for the learning process.